The Influence of the NHT Assisted Media Model and Learning Motivation on Learning Outcomes of Citizenship Education - Fauziah Nasution; Deny Setiawan; Wildansyah Lubis (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
The aim of this research is to know the influence of NHT assisted media model and learning motivation on learning outcomes of citizenship education. This research will be implemented in 5th grade of Primary School at SD IT Tahfizhil Quran YIC SU, which is located at Jalan Haji Hospital. This school has an "A" accreditation. The research activities were carried out in the first semester of the 2018-2019 Academic Year, setting the research schedule according to the schedule set by the school principal. The subject matter selected in this study is "Diversity" which is the material in the class IV syllabus that is being studied in the semester.